2011
DOI: 10.4174/jkss.2011.81.suppl1.s34
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted distal gastrectomy for early gastric cancer and laparoscopic cholecystectomy for gallstone with situs inversus totalis: a case report

Abstract: We report our case of laparoscopy-assisted distal gastrectomy with D1 + β lymph node dissection for a patient with early gastric cancer and laparoscopic cholecystectomy for gallstone with situs inversus totalis. A superficial elevated lesion was found on the lesser curvature of the antrum. The preoperative diagnosis was cStage IA (cT1, cN0, cH0, cP0, cM0). A 1 cm-sized gallstone was found in the fundus through upper abdominal ultrasound. A laparoscopy-assisted distal gastrectomy with standard D2 lymph node dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…It has been stated that multiple molecules or genes determine laterality and act in a region-or organ-specific manner [10]. Several studies reported about situs inversus totalis that all thoracic and abdominal viscera were completely transposed [2,4,8,[11][12][13][14][15][16]. However, Mano et al (2006) [17] reported that situs inversus with unclearly inverted morphology, neutral laterality (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…It has been stated that multiple molecules or genes determine laterality and act in a region-or organ-specific manner [10]. Several studies reported about situs inversus totalis that all thoracic and abdominal viscera were completely transposed [2,4,8,[11][12][13][14][15][16]. However, Mano et al (2006) [17] reported that situs inversus with unclearly inverted morphology, neutral laterality (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…However, the attitude has been changed over the last several years. Few case reports on patients with situs inversus who had underwent cholecystectomy, distal gastrectomy due to the gastric carcinoma using the laparoscopic method, gastrectomy with cholecystectomy, liver resection, splenectomy and lung tumor have been published so far [17][18][19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with other anomalies such as polysplenia, Ivemark-Kartagener syndrome and biliary atresia [11][12][13][14] . Due to a possible onset of complications within the associated anomalies, a particular attention was also paid to it in other surgical interventions, particularly in abdominal surgery [15][16][17][18][19][20][21][22][23] . However, the attitude has been changed over the last several years.…”
Section: Discussionmentioning
confidence: 99%
“…9 Many laparoscopic procedures (eg, cholecystectomy, gastrectomy, colectomy, and splenectomy) have been reported to be performed safely in patients with SIT, despite the fact that there are some technical difficulties owing to mirror image of anatomy. [10][11][12][13][14] We found few articles describing kidney donation in patients with complete situs inversus. Black and associates 15 reported the first case, and they used hand-assisted laparoscopic technique for the right side.…”
Section: Discussionmentioning
confidence: 99%